2021
DOI: 10.3389/fpsyt.2021.640218
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Treatment of Kratom Use Disorder With a Classical Tricyclic Antidepressant

Abstract: Kratom or Mitragyna speciosa (Korth.) is an evergreen tree of the coffee family native to South-East Asia and Australasia. It is used by locals recreationally to induce stimulant and sedative effects and medically to soothe pain and opiate withdrawal. Its leaves are smoked, chewed, or infused, or ground to yield powders or extracts for use as liquids. It contains more than 40 alkaloids; among these, mitragynine and 7-hydroxymitragynine are endowed with variable mu, delta, and kappa opioid stimulating propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Because we assessed SUD criteria only for some drugs (which did not include kratom for most respondents), we cannot directly compare our findings to those of studies that attempted to operationalize kratom-use disorder. 35 , 55 , 85 - 87 …”
Section: Discussionmentioning
confidence: 99%
“…Because we assessed SUD criteria only for some drugs (which did not include kratom for most respondents), we cannot directly compare our findings to those of studies that attempted to operationalize kratom-use disorder. 35 , 55 , 85 - 87 …”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of kratom may produce physical and psychological effects that are very similar to its withdrawal syndrome, that is, anxiety, irritability, mood, eating, and sleep disorders, other than physical symptoms resembling opiate withdrawal (Vento, et al, 2021) A cross-sectional clinical study in Malaysia found that chronic abusers on kratom don't have significant social functioning impairment and kratom is a less harmful substitute to opioids (Singh et al, 2015). Additionally, chronic heavy mitragynine consumption was not associated with altered biochemical levels, although it may propably increase cardiovascular risks (Singh et al, 2020).…”
Section: Kratom As Addictive Substancementioning
confidence: 99%
“…30,54,63 Maintenance treatment for kratom dependence and addiction has also been investigated, with reports of success using buprenorphine-naloxone, naltrexone, and clomipramine. 11,54,55,62,64…”
Section: Usage Clinical Effects and Adverse Effectsmentioning
confidence: 99%
“…30,54,63 Maintenance treatment for kratom dependence and addiction has also been investigated, with reports of success using buprenorphine-naloxone, naltrexone, and clomipramine. 11,54,55,62,64 GOVERNMENTAL REGULATION In 2016, the DEA announced aggressive plans to classify mitragynine as a schedule I substance, but vocal kratom advocates effectively thwarted this effort. 70,71 The following year, the DEA took less aggressive measures and listed kratom as a "drug of concern," released a warning against its use, and cited high potential for developing dependence, addiction, overdose, and withdrawal, after identifying more than 50 deaths associated with kratom.…”
Section: Potentiation Of Neuromuscular Blockadementioning
confidence: 99%